Evaluation of Efficacy of Arginine Calcium Carbonate Versus Potassium Nitrate Paste in the treatment of Dentinal Hypersensitivity - Zoha Wisal Khan, Sana Ahmad, Ayousha Iqbal, Saad Mansoor, Nida Fatima, Zainab Javed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Dentin hypersensitivity (DH) is a frequent oral health condition that affects one or more teeth in many adults characterized by a severe pain of exposed dentin to an external stimulation. The present study aimed to assess the efficacy of arginine calcium carbonate versus potassium nitrate paste in the dental hypersensitivity treatment. Materials and Methods: This randomized controlled trial was carried out on 56 subjects in the Department of Dentistry of a Tertiary Care Hospital from January 2021 to December 2022. All the subjects were divided into two groups: Group-I as test group (toothpaste containing 8% arginine and calcium carbonate and toothpaste containing 5% potassium nitrate) and Group-II as control group. Schiff Cold Air Sensitivity scale was used for recording the air blast stimuli at baseline and DH scores were used for tactile stimuli on visual analog scale immediately post scaling after desensitizing paste application. Subjects were followed-up for 1 month. SPSS version 27 was used for data analysis. Results: The subjects in test-group had decreased sensitivity values 2.52± 0.31 at baseline to post scaling after desensitizing paste application value of 1.87 ± 0.28. The sensitivity further reduced to 1.12 ± 0.39 after paste use for one month and 1.07± 0.42 after one month cessation of its use. Both tooth pastes significantly alleviated dental hypersensitivity. The arginine and calcium carbonate presented better clinical response than potassium nitrate paste after 1 month assessment. Conclusion: The arginine and calcium carbonate showed better clinical response than potassium nitrate paste in terms of long-term reduction in dentinal hypersensitivity symptoms. Keywords: Dentinal hypersensitivity, Arginine and calcium carbonate, Potassium nitrate, Efficacy, Dental Pulp.